Methylenetetrahydrofolate Reductase (MTHFR) C677T Polymorphism and Subacute Combined Degeneration: Revealing a Genetic Predisposition - Zhang, Xin; Hou, Chen; Liu, Peng; Chen, Li; Liu, Yue; Tang, Peng; Li, Rui (Frontiers in Neurology, 2019)
Vitamin B12 deficiency has been regarded as the prevailing cause of subacute combined degeneration of the spinal cord (SCD). Nevertheless, the genetic predisposition to SCD still remains unclear. The aim of this study was to explore the association between the methylenetetrahydrofolate reductase gene (MTHFR) C677T polymorphism and SCD. We investigated the MTHFR C677T polymorphism in the SCD patients. The distribution of MTHFR C677T genotypes was significantly different between the SCD patients and age-matched controls. Furthermore, the T allele frequency was markedly increased in SCD as compared with the controls. In addition, the plasma homocysteine concentrations in subjects with the TT genotype were significantly elevated as compared to those of the CC genotype. A Logistic regression analysis revealed that the MTHFR C677T genotype (TT versus CT and CC) and vitamin B12 deficiency were the risk factors for SCD. Our findings indicate that the T allele of the MTHFR C677T as a strong genetic predisposition to SCD and provide evidence for the association between the MTHFR C677T polymorphism and SCD. These data reveal a potential mechanism underlying SCD etiology.